Role of Nitric Oxide in Extracellular Matrix Metabolism and Inflammation in Diabetic Wound Healing - Sylvia, Victor L.; Myers, Audra D.; Seifert, Brandon M.; Stehly, Eric M.; Weathers, Michael A.; Dean, David D.; LaFontaine, Javier (IntechOpen, 2011)
None